Soil nutrient status of KwaZulu-Natal savanna and grassland biomes causes variation in cytokinin functional groups and their levels in above-ground and underground parts of three legumes - Aremu, Adeyemi Oladapo; Plačková, Lenka; Egbewale, Samson Olufemi; Doležal, Karel; Magadlela, Anathi (Physiology and molecular biology of plants, 2021)
UNLABELLED: Cytokinins (CKs) are involved in several developmental stages in the life-cycle of plants. The CK content in plants and their respective organs are susceptible to changes under different environmental conditions. In the current study, we profiled the CK content in the above and underground organs of three legumes (Lessertia frutescens, Mucuna pruriens and Pisum sativum) grown in soils collected from four locations (Ashburton, Bergville, Hluhluwe and Izingolweni) in KwaZulu-Natal province, South Africa. The quantified CK contents in the three legumes were categorized on the basis of their side chains (isoprenoid, aromatic and furfural) and modifications (e.g. free bases and glucosides). Legume and soil types as well as their interaction significantly influenced the concentrations of CKs. Lessertia frutescens, Mucuna pruriens and Pisum sativum had CK content that ranged from 124-653, 170-670 and 69-595 pmol/g DW, respectively. Substantial quantity (> 600 pmol/g DW) of CK were observed in plants grown in Bergville (above-ground part of Lessertia frutescens) and Izingolweni (underground part of Mucuna pruriens) soils. A total of 28 CK derivatives observed in the legumes comprised of isoprenoid (22), aromatic (5) and furfural (1) side-chain CKs. However, the 16 CK derivatives in Mucuna pruriens were isoprenoid-type based on the side-chain. Generally, a higher ratio of cis-zeatin (cZ) relative to the trans-zeatin (tZ) was evident in the above-ground part of Lessertia frutescens and Pisum sativum for the four soil treatments. In terms of functional and physiological importance of the CKs, the free bases (active form) and ribosides (translocation form) were the most abundant CK in Lessertia frutescens and Pisum sativum. However, N-glucoside, a deactivation/detoxicification product was the most dominant CK in Mucuna pruriens from Hluhluwe and Izingolweni soils. The total CKs in the underground parts of the legumes had a positive significant correlation with the total phosphorus and nitrogen content in the plant as well as the soil nitrogen. Overall, the CK profiles of the legumes were strongly influenced by the soil types. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12298-021-01021-2.
Keywords: Rhizobia; Biomass; Nodulation; Fabaceae; Nitrogen fixation; Phytohormones